‘Theory’ for teacher practice: A typology of application tasks in teacher education - Shalem, Y.; Rusznyak, L. (South African Journal of Higher Education, 2016)
Debates about the relation between educational theory and teaching practice are embodied in assessment tasks that prompt student teachers to relate theoretical concepts and simulated or directly experienced practice-based contexts in relation to one another. To establish clarity on the ways in which theory and practice can be positioned in relation to one another in application tasks, we revisit the debate between Paul Hirst and Wilfred Carr (2005) about the role of theory in and for education. We provide examples of assessment tasks and then present a typology showing how such tasks demarcate conceptual and contextual objects of study in ways that are more or less visible to students. We argue that the more visibly the concepts are demarcated, the greater the possibilities are for student teachers to develop systematized bodies of educational knowledge that are able to provide organizing insights into their developing practice. While we concede that there might be valid pedagogical reasons for doing so, we argue that when conceptual objects are less visible to students, the underlying message that is transmitted to students is that educational theory is not specialized knowledge and is not distinctively different from their common-sense perspectives. This approach is less likely to promote their acquisition of systematized knowledge for and of practice.